A novel synthetic lipopeptide is allergy‐protective by the induction of LPS‐tolerance. Issue 7 (21st June 2013) - Stiehm, M.; Peters, K.; Wiesmüller, K.‐H.; Bufe, A.; Peters, M.
Summary Background Exposure to the environment of traditional farms can protect children from some allergic disease. Due to this exposure, TLR2 expression in these children is increased. TLR2 ligands derived from gram‐positive bacteria are found in the dust of these farms. Objectives We proved whether a synthetic lipopeptide binding to the TLR1/2 heterodimer is able to protect from allergic disease in two different murine models of allergy. We also investigated the immunological mechanisms underlying the protective properties of the lipopeptide. Methods We synthesized a lipopeptide derived from a germination lipoprotein of Bacillus cereus (LPGerD). We evaluated the immunomodulatory activity of LPGerD in a murine model of systemic sensitization (OVA/Alum) and in a model in which mice were sensitized with OVA pulsed bone‐marrow‐derived dendritic cells (BMDCs) via the airways. Furthermore, the induction of LPS tolerance was studied. Results Treatment of mice with LPGerD in a mouse model of asthma led to protection against sensitization and airway inflammation. Similarly, bone‐marrow‐derived dendritic cells (BMDCs) pre‐treated with LPGerD were not able to prime mice for allergic immune response. We observed that pre‐treatment with LPGerD led to the induction of a LPS‐tolerant state in BMDCs. These cells secreted markedly lower amounts of pro‐inflammatory cytokines upon LPS stimulation. Furthermore, we observed an up‐regulation of IRAK‐M mRNA in BMDCs pre‐treated with LPGerD. Conclusions and Clinical Relevance Our results suggest that induction of a LPS‐tolerant state in antigen‐presenting cells (APCs) may contribute to the protective effect of a farming environment. TLR2 agonists similar to those appearing in cowshed dust extracts, such as our synthetic LPGerD, lead to the ignorance of the LPS stimulus, which is important for the activation of APCs to mount a Th2 immune response. This substance might be a promising candidate for allergy‐preventive treatments as LPGerD had only low pro‐inflammatory characteristics.